2014
DOI: 10.1037/dec0000006
|View full text |Cite
|
Sign up to set email alerts
|

The affect gap in risky choice: Affect-rich outcomes attenuate attention to probability information.

Abstract: It has been suggested that people decide differently when faced with affect-rich prospects (e.g., medical side effects) than with prospects triggering more moderate amounts of affect (e.g., monetary losses). Does this potential impact of affect on risky decision making even result in preference reversals? And if so, how do the cognitive processes underlying the respective decisions differ? Using a within-subjects design, the current research contrasted choices between prospects with relatively affect-rich outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
141
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 88 publications
(157 citation statements)
references
References 74 publications
15
141
0
1
Order By: Relevance
“…(1820) Emotional responses to side effects, in turn, have been shown to decrease people’s use of information about the probability of occurrence of the side effects. (21) Patients’ evaluations of treatment options may thus be based less on a deliberative calculation of risks and benefits and more on a spontaneous and affectively-based judgment about the medication quality. These spontaneous reactions, in turn, could act as a frame through which subsequent beliefs about the medication are formed and decisions made.…”
Section: Introductionmentioning
confidence: 99%
“…(1820) Emotional responses to side effects, in turn, have been shown to decrease people’s use of information about the probability of occurrence of the side effects. (21) Patients’ evaluations of treatment options may thus be based less on a deliberative calculation of risks and benefits and more on a spontaneous and affectively-based judgment about the medication quality. These spontaneous reactions, in turn, could act as a frame through which subsequent beliefs about the medication are formed and decisions made.…”
Section: Introductionmentioning
confidence: 99%
“…According to CPT, responses to risky alternatives (which lead to different outcomes with some probability) are a function of several factors, including a person's sensitivity to outcome and probability information and his or her relative weighting of losses and gains ("loss aversion"). In the model, the degrees of outcome and probability sensitivity and the amount of loss aversion can be quantified by free parameters, and several studies have fitted CPT parameters to investigate how differences in age (Harbaugh, Krause, & Vesterlund, 2002), gender (e.g., Fehr-Duda, De Gennaro, & Schubert, 2006, delinquency (Pachur, Hanoch, & Gummerum, 2010), or affect (Pachur, Hertwig, & Wolkewitz, 2014) influence risky decision making. For such applications of computational modeling, it is often essential to obtain a set of parameter estimates for each individual.…”
mentioning
confidence: 99%
“…However, when faced with emotion or affect-charged decisions, evidence suggests that people systematically choose the optimal option less often [28]. And others have suggested that the impact of probability information may be attenuated in affect-rich choices [34]. Though this was not explicitly studied in this set of tasks, the affect involved in choices made by physicians in health-care decisions may be different than that of non-clinicians, and may impact the measured risk preferences in these situations.…”
Section: Discussionmentioning
confidence: 99%